PATHOLOGICAL STUDIES ON NATURAL INFECTION OF PORCINE REPRODUCTIVE AND RESPIRATORY SYNDROME VIRUS AND CO-INFECTION WITH PORCINE CIRCOVIRUS 2 ASSOCIATED POST-WEANING MULTI-SYSTEMIC WASTING SYNDROME AMONG SWINE HERDS OF KERALA, SOUTHERN INDIA - Sairam R; Dhanush Krishna Balakrishnan-Nair; Krithiga K; Sajitha IS; Priya PM; Chintu Ravishankar; Devi SS; Anoopraj R (Exploratory Animal and Medical Research)
Porcine reproductive and respiratory syndrome virus (PRRSV) infection is an endemic, economically important disease affecting the swine industry worldwide. Since its first outbreak in 2013, this disease has been rapidly spreading to different parts of India. The objectives of this study were to screen PRRSV among the swine population in Kerala, India, and to understand its pathological characteristics. Pathological investigation revealed lesions in respiratory and lymphoid organs, and viral antigen distribution was demonstrated using immunohistochemistry (IHC). Based on molecular screening using reverse transcriptase polymerase chain reaction (RT-PCR) and immunohistochemistry (IHC), eight samples tested positive for PRRSV. These results were corroborated by gross and histopathological findings. Post-weaning multi-systemic wasting syndrome (PMWS) was also observed in two cases of PCV2-positive pigs co-infected with PRRSV. Additionally, the findings confirmed the mutual association of PRRSV and PCV-2 in PMWS among swine herds in southern India. The study identified the PRRSV strain as a Type II North American genotype (PRRSV-2). Further investigation of strains that are currently circulating in India is crucial to fully understand the diversity, distribution, and evolution of the virus.